Aktivitas Enzimatis Biakan Kapang Aspergillus Section Nigri DUCC (Diponegoro University Culture Collection) Dan Identifikasi Molekuler Isolat Potensial - Sabrini, Zalia; Rukmi, Isworo; Ferniah, Rejeki Siti (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2021)
The enzyme amylase, cellulase and protease are an extracellular enzymes are many produced by microorganisms such as fungi Aspergillus section Nigri. This research aims to find out the potential biakanes of Aspergillus section Nigri DUCC collection (Diponegoro University Culture Collection) which is capable to produce some enzymes that consists of amylase, protease and celullase and also identification in molecular based. Activity enzymatic assay of Aspergillus section Nigri withÂ semi-quantitative method using selective medium, CMC for cellulolytic, Starch agar 1% for amylolytic and Skim Milk agar for proteolytic. Biakane potential is determined by looking at the Enzymatic Index (EI) is highest for all of three enzyme. Molecular identification is using the universal primer ITS4 and ITS5. The results showed that the culture of DUCC K207Â has high activity for all of three enzyme. Index enzymatic of isolate DUCC K207 , 1.55 mm for amylolytic, 1.49 mm for cellulolytic and 1, 24 mm for proteolytic. Result of molecular identification DUCC K207Â known as Aspergillus niger that has 100% similarity with Aspergillus niger MH 109325.1.